2017
DOI: 10.1016/j.alcohol.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles for ncRNAs in alcohol use disorders

Abstract: Chronic alcohol exposure produces widespread neuroadaptations and alterations in gene expression in human alcoholics and animal models. Technological advances in the past decade have increasingly highlighted the role of non-protein-coding RNAs (ncRNAs) in the regulation of gene expression and function. These recently characterized molecules were discovered to mediate diverse processes in the central nervous system, from normal development and physiology to regulation of disease, including alcoholism and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 95 publications
1
35
4
Order By: Relevance
“…These data suggest that serum GATA6-AS level may be used for the diagnosis of cervical squamous cell carcinoma. It is understood that the expression of certain lncRNAs is affected by various factors, including aging (21), alcohol consumption (22) and tobacco abuse (23). In the present study, serum levels of GATA6-AS demonstrated no significant association with age, drinking habit or smoking habit, which indicates the high stability of serum GATA6-AS as a potential biomarker of disease.…”
Section: Discussioncontrasting
confidence: 60%
“…These data suggest that serum GATA6-AS level may be used for the diagnosis of cervical squamous cell carcinoma. It is understood that the expression of certain lncRNAs is affected by various factors, including aging (21), alcohol consumption (22) and tobacco abuse (23). In the present study, serum levels of GATA6-AS demonstrated no significant association with age, drinking habit or smoking habit, which indicates the high stability of serum GATA6-AS as a potential biomarker of disease.…”
Section: Discussioncontrasting
confidence: 60%
“…Although this cross‐sectional study only used self‐reported alcohol consumption, and only 3 Caucasian and 13 African men volunteered for this study, animal studies have partly confirmed this effect . More specifically, animal data indicate the complexity of epigenetic changes, not only involving methylation alterations, but also altered chromatin remodeling and different classes of non‐coding RNAs (ncRNAs) …”
Section: Does the Environment Influence Male Fertility And Sperm Charmentioning
confidence: 94%
“…Bulk and scRNA-seq studies often exclude non-coding RNAs from their analyses (3,8,35) . However, the importance of ncRNAs is becoming increasingly apparent, not only in alcohol dependence (36) , but in brain physiology in general (37) , and these RNAs were therefore included in our data.…”
Section: Differential Expression and Pathway Analysismentioning
confidence: 99%